Your Brain on Comics: A Cognitive Model of Visual Narrative Comprehension. (8th April 2019) - Cohn, Neil
Abstract: The past decade has seen a rapid growth of cognitive and brain research focused on visual narratives like comics and picture stories. This paper will summarize and integrate this emerging literature into the Parallel Interfacing Narrative‐Semantics Model (PINS Model)—a theory of sequential image processing characterized by an interaction between two representational levels: semantics and narrative structure. Ongoing semantic processes build meaning into an evolving mental model of a visual discourse. Updating of spatial, referential, and event information then incurs costs when they are discontinuous with the growing context. In parallel, a narrative structure organizes semantic information into coherent sequences by assigning images to categorical roles, which are then embedded within a hierarchic constituent structure. Narrative constructional schemas allow for specific predictions of structural sequencing, independent of semantics. Together, these interacting levels of representation engage in an iterative process of retrieval of semantic and narrative information, prediction of upcoming information based on those assessments, and subsequent updating based on discontinuity. These core mechanisms are argued to be domain‐general—spanning across expressive systems—as suggested by similar electrophysiological brain responses (N400, P600, anterior negativities) generated in response to manipulation of sequential images, music, and language. Such similarities between visual narratives and other domains thus pose fundamental questions for the linguistic and cognitive sciences. Abstract : Visual narratives like comics involve a range of complex cognitive operations in order to be understood. The Parallel Interfacing Narrative‐Semantics (PINS) Model integrates an emerging literature showing that comprehension of wordless image sequences balances two representational levels of semantic and narrative structure. The neurocognitive mechanisms that guide these processes are argued to overlap with other domains, such as language and music.